Interaction of Synthetic Human SLURP-1 with the Nicotinic Acetylcholine Receptors. Issue 1 (December 2017) - Durek, Thomas; Shelukhina, Irina; Tae, Han-Shen; Thongyoo, Panumart; Spirova, Ekaterina; Kudryavtsev, Denis; Kasheverov, Igor; Faure, Grazyna; Corringer, Pierre-Jean; Craik, David; Adams, David; Tsetlin, Victor
Abstract Human SLURP-1 is a secreted protein of the Ly6/uPAR/three-finger neurotoxin family that co-localizes with nicotinic acetylcholine receptors (nAChRs) and modulates their functions. Conflicting biological activities of SLURP-1 at various nAChR subtypes have been based on heterologously produced SLURP-1 containing N- and/or C-terminal extensions. Here, we report the chemical synthesis of the 81 amino acid residue human SLURP-1 protein, characterization of its 3D structure by NMR, and its biological activity at nAChR subtypes. Radioligand assays indicated that synthetic SLURP-1 did not compete with [125 I]-α-bungarotoxin (α-Bgt) binding to human neuronal α7 andTorpedo californica muscle-type nAChRs, nor to mollusk acetylcholine binding proteins (AChBP). Inhibition of human α7-mediated currents only occurred in the presence of the allosteric modulator PNU120596. In contrast, we observed robust SLURP-1 mediated inhibition of human α3β4, α4β4, α3β2 nAChRs, as well as human and rat α9α10 nAChRs. SLURP-1 inhibition of α9α10 nAChRs was accentuated at higher ACh concentrations, indicating an allosteric binding mechanism. Our results are discussed in the context of recent studies on heterologously produced SLURP-1 and indicate that N-terminal extensions of SLURP-1 may affect its activity and selectivity on its targets. In this respect, synthetic SLURP-1 appears to be a better probe for structure-function studies.